5 Clinical Evaluation of the Abuse Potential of Buprenorphine/Samidorphan Combination. (12th March 2019) - Cutler, Andrew J.; Mathew, Sanjay J.; DeBakey, Michael E.; Setnik, Beatrice; Nangia, Narinder; Stanford, Arielle D.; Pathak, Sanjeev
Abstract: Introduction: Buprenorphine (BUP)/samidorphan (SAM) combination is an opioid system modulator being investigated as an adjunctive treatment for major depressive disorder (MDD). BUP/SAM is a fixed-dose combination of BUP, a partial µ-opioid receptor agonist and κ-opioid receptor antagonist, and SAM, a µ-opioid receptor antagonist added to address the abuse and dependence potential of BUP. 1, 2 Study Objective: We assessed the effects of SAM on the abuse potential of BUP in the BUP/SAM combination in two ways: (1) a human abuse potential (HAP) study in volunteers; and (2) an evaluation of the clinical experience across studies of patients with MDD. Methods: Study 212 (ClinicalTrials.gov ID: NCT02413281) was a HAP study in nondependent, recreational, adult opioid users. Following a qualification period, participants were randomized to 6 treatments in a blinded, crossover design: placebo (PBO), BUP/SAM at the target therapeutic dose (BUP/SAM 2mg/2mg), at 8mg/8mg and 16mg/16mg, and BUP alone (8mg and 16mg). The primary endpoint was maximum effect (Emax) for "At The Moment" Drug Liking Visual Analog Scale (VAS). The clinical program for BUP/SAM included 4 PBO-controlled studies of patients with MDD (n=961). Pooled safety data were evaluated for adverse events (AEs) that may be associated with abuse, dependence, or withdrawal, as well as for objective signs of withdrawal with the Clinical Opioid Withdrawal Scale (COWS). Results: In Study 212 (n=38), Emax Drug Liking VAS scores for the BUP/SAM 2mg/2mg dose were similar to those for PBO (median within-subject difference [90% CI]: 2.5 [0.0–9.0]). Emax Drug Liking VAS scores for all BUP/SAM dose groups, including supratherapeutic doses, were significantly lower than those observed for either of the BUP doses. The supratherapeutic doses of BUP/SAM (8mg/8mg and 16mg/16mg) had higher Emax Drug Liking VAS scores than PBO, but the differences were small. In the MDD controlled studies, the incidence of euphoria-related AEs was low for BUP/SAM 2mg/2mg and PBO (1.6% vs 0.2%, respectively) and there was no evidence of abuse or dependence behavior. Euphoria-related events typically occurred with treatment initiation and resolved with continued treatment. There was minimal evidence of withdrawal by reported AEs or COWS assessment. Conclusions: These findings indicate that SAM mitigates the abuse potential of BUP in the BUP/SAM combination. Funding Acknowledgements: Alkermes, Inc.